Internet Banking Adoption in South Africa: The Mediating Role of Consumer Readiness - C, Aguidissou O; Shambare, Richard; R, Rugimbana (Journal of Economics and Behavioral Studies, 2017)
The recent rapid development of Internet banking (IB) around the world is not without certain challenges. For instance while a majority of banking SSTs (Self Service Technologies, e.g. ATMs and debit cards) have been well received by the South African market, consumers seem sceptical towards Internet banking. This paper seeks to test various conceptual frameworks of consumer adoption patterns of IB with the view of a framework with the greatest explanatory power for the South African market. To achieve the stated objective of a framework for IB adoption in South Africa, this paper suggests an approach not yet undertaken, according to the literature review conducted, within the South African retail banking industry – investigating a comparison of the predictive efficacy of two common groupings of variables most cited in the consumer behaviour literature as important determinants of adoptive behaviour in SSTs. These are: perceptions of innovation characteristics and consumer readiness (CR) variables. Therefore, the primary objective of this article is the consideration of this gap within the body of knowledge around South African consumers’ IB adoption behaviour. Through a descriptive quantitative analysis of 1516 large sample size, innovation characteristics as consumer’s perceptions (complexity, perceived risk notably) or views (endogenous variables) were found with greatest predictive power over IB adoption, in the South African consumer market context. This finding is therefore for marketers (particularly in South Africa) a set of useful tools that can be relevant to promote the adoption of IB.